Role of Th22 Cells in the Pathogenesis of Autoimmune Diseases - Jiang, Qi; Yang, Guocan; Xiao, Fan; Xie, Jue; Wang, Shengjun; Lu, Liwei; Cui, Dawei (Frontiers in Immunology, 2021)
Upon antigenic stimulation, naïve CD4+T cells differentiate into different subsets and secrete various cytokines to exert biological effects. Th22 cells, a newly identified CD4+T cell subset, are distinct from the Th1, Th2 and Th17 subsets. Th22 cells secrete certain cytokines such as IL-22, IL-13 and TNF-α, but not others, such as IL-17, IL-4, or interferon-γ (IFN-γ), and they express chemokine receptors CCR4, CCR6 and CCR10. Th22 cells were initially found to play a role in skin inflammatory diseases, but recent studies have demonstrated their involvement in the development of various autoimmune diseases. Here, we review research advances in the origin, characteristics and effector mechanisms of Th22 cells, with an emphasis on the role of Th22 cells and their main effector cytokine IL-22 in the pathogenesis of autoimmune diseases. The findings presented here may facilitate the development of new therapeutic strategies for targeting these diseases.